Stanislas Breton's Use of Neoplatonism to Interpret the Cross in a Postmodern Setting - Porter, Jacquelyn (Heythrop journal, 1998)
In the aftermath of the debate between Derrida and Levinas on Hebraism and Hellenism, Christian thought that retains a place for philosophy is often regarded as “Graeco-Christian”, a monolithic system with an unfortunate history. The work of the French philosopher Stansilas Breton suggests that the reality is more complex. In Le Verbe et la croix (Paris, Desclee, 1981), he examines the function of the term logos staurou in Paul, arguing that this untranslatable term stands as a question mark in a world of language that could only speak “Jew” or “Greek”. Far from being a sign of Christian superiority, the cross signals an imperative for dispossession intrinsic to Christian language. In its “nothingness” the cross functions as a principle of critique that makes innovation and engagement possible. Thus while the cross involves negation it moves beyond negative theology. Drawing upon neoplatonist philosophy, Breton delineates the way in which the cross makes possible “the writing of the self in the world”. This paper draws upon Breton's understanding of the function of the cross to argue that the heritage of Athens endures and must be re-thought, always recognizing the limits of all human language. After examining Breton's understanding of the logos staurou, it relates this notion to his broader understanding of revelation as “writing”. Finally it shows how Breton appeals to neoplatonist meonotology to speak in more universal terms of the need for a principle of dispossession at the heart of all religious language. For Christians the cross is this principle, enabling human beings to be causes of themselves who engender new being.